DOCK1 regulates the malignant biological behavior of endometrial cancer through c-Raf/ERK pathway - Shangdan Xie; Yanshan Jin; Jiakun Wang; Jingwei Li; Mengjia Peng; Xueqiong Zhu (BMC Cancer, 2024)
Abstract Background The effect of DOCK1 gene on the biological behavior of endometrial carcinoma cells and its related pathway has not been reported. Methods The immunohistochemical method and western blot were utilized to analyze DOCK1 protein expression in endometrial tissues and cells, respectively. CCK-8, BrdU, transwell and flow cytometry were performed to analyze the effect of DOCK1 expression changes on the viability, proliferation, invasion, migration and apoptosis of endometrial cancer cells, respectively. The effects of DOCK1 gene on Bcl-2, MMP9, Ezrin, E-cadherin and c-RAF/ERK1/2 signaling pathway were evaluated by western blot. The xenograft models were constructed to analyze the effect of DOCK1 in vivo. Results DOCK1 expression was increased in endometrial cancer tissues and cells compared with those in normal adjacent tissues and cells. DOCK1 knockout could inhibit the malignant biological behavior of endometrial cancer cells, while DOCK1 overexpression played the opposite effect. The expression of E-cadherin was upregulated and those of MMP9, Ezrin, Bcl-2, p-c-RAF (S338) and p-ERK1/2 (T202/Y204) were downregulated after DOCK1 knockout, while DOCK1 overexpression played the opposite effect. Additionally, Raf inhibitor LY3009120 reversed the function of DOCK1 on malignant biological behavior. In vivo experiment results showed that the growth and weight of transplanted tumors in nude mice were inhibited after DOCK1 knockout. The changes of E-cadherin, MMP9, Ezrin and Bcl-2 expressions in the transplanted tumors were consistent with those in vitro. Conclusion DOCK1 could enhance the malignant biological behavior of endometrial cancer cells, which might be through c-RAF/ERK1/2 signaling pathways in vitro and in vivo.